Thermoacoustic energy conversion in a square duct - Harikumar, Govind (2019)
The present study aims to demonstrate the thermoacoustic energy conversion phenomenon in a standing wave resonator driven by a commercial loudspeaker with a stack made of plastic straws and atmospheric air as the working fluid. The system is driven at resonance frequency of 70 Hz with the stack kept in the middle section of the resonator and a temperature difference of 14.1℃ was produced between the ends of the stack at a drive ratio of 3.57 %. The hot end reached a temperature of 36.5℃ and the cold end reached a temperature of 22.4℃ at the highest drive ratio. Moving the stack towards the end of the resonator reduces the temperature difference produced showing the influence of stack position. Thermoacoustic devices offer an environment-friendly solution to utilize waste heat or renewable energy sources, to upgrade low grade heat or generate cooling or produce electricity using acoustic-electric transducers. This study is done as a pre-cursor, to develop a relatively inexpensive prototype for studying non-linear effects at high drive ratios seen in thermoacoustic devices, which are known to reduce their performance.